An active equalization method for series-parallel battery pack based on an inductor. (1st August 2023) - Guo, Xiangwei; Wu, Qi; Xing, Cheng; Qian, Wei; Zhao, Yunji
Abstract: The equalization topologies based on inductive energy storage have high equalization accuracy and perfect functionality, but often have more complex structure and control method. To overcome this problem, an active equalization method based on an inductor is proposed for the series-parallel battery pack. The energy storage device responsible for energy transfer requires only one inductor and the topology is simple and low cost. Combining diodes and MOSFETs to form a switching array reduces the cost of the equalization topology while increasing the fault tolerance of the control signal and making equalization control simpler. First, the working principle and parameter design process of the topology are described, and the control strategy adapted to it is proposed on this basis. Second, based on the simulation models, the variation law of the efficiency and speed of the proposed equalization method influenced by inductance and switching frequency is analyzed, and by comparing the new equalization method with similar methods, it is verified that the new equalization method is simple in structure, low in cost, and convenient in control. Final, by building an experimental platform for "four-series and two-parallel" battery pack, the effectiveness of the new equalization method is verified. Highlights: The characteristics of the new equalization method can be summarized as follows: The energy storage device only needs one inductor, and the balanced energy can be transferred between any cell or unit in the series-parallel battery pack. Combining diodes and MOSFETs to form a switching array reduces the cost of the equalization topology while increasing the fault tolerance of the control signal.